The Hyperlocal data documentation for farmer empowerment through phygital services - Shireesha, D; Jagan, M R M; Prasad, P (Plant Science Today, 2026)
The study explores the documentation and utilisation of hyperlocal agricultural data through the mobile agri support services (MASS) initiative implemented in 2024 in 3 aspirational districts of Telangana viz., Kumuram Bheem Asifabad, Jayashankar Bhupalpally, Khumuram and Bhadradri Kothagudem. The initiative integrates physical and digital (phygital) approaches to enhance the accessibility, precision and timeliness of agricultural services for smallholder farmers. A total of 1000 farmers were surveyed using participatory rural appraisal (PRA) techniques, focus group discussions (FGDs) and structured interviews to assess socio-economic profiles, constraints and technology adoption patterns. This study analysed hyperlocal agricultural data from 6 villages in 3 aspirational districts of Telangana covering 1465 households and 1418 farmers cultivating 150.3–385.4 ha per village with limited irrigation (10.2–200.3 ha). Paddy, cotton and red gram were the major crops, with borewells as the main irrigation source and no marketing facilities. The FGDs revealed that 83–100 % of farmers faced high input costs, price fluctuations, weak extension services, limited technology access and allied sector constraints, while socio-economic data showed predominance of middle-aged, marginal, low-income farmers with high dependence on moneylenders and low access to agro-advisories, indicating significant structural and institutional gaps. The study concludes that hyperlocal data, when integrated within a phygital extension framework, enables need-based advisories, efficient resource utilisation and inclusive service delivery. The MASS model demonstrates a scalable approach to strengthening agricultural extension, fostering farmer empowerment, institutional innovation and profitability through real-time, localised data-driven interventions.